KEWAJIBAN PEMENUHAN HAK-HAK ANAK PASCA-PERCERAIAN BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DI PENGADILAN AGAMA PEKANBARU - Muhammad Azani; Hasan Basri; Siti Halimah (Jotika Research in Business Law, 2024)
The rights and obligations of the husband and wife after the divorce are contained in Article 41 of the Marriage Law, but currently many ex-husbands forget the obligation to provide for children after the divorce so that many ex-wives demand this obligation. Therefore, the authors formulate the problem as follows: 1) How is the implementation of the fulfillment of children's rights after the divorce of their parents based on Law No. 1 of 1974 concerning Marriage in the Pekanbaru Religious Court?, 2) What are the obstacles in granting and fulfilling rights -children's rights after divorce?, 3) What about post-divorce, the child's rights are not fulfilled by his biological father? The aims of this study are as follows: 1) To find out the implementation of the fulfillment of children's rights after divorce based on Law Number 1 of 1974 concerning Marriage, 2) To find out the factors that become obstacles in the implementation of the granting of children's rights after divorce, 3) To find out the legal remedies that can be taken for children's rights that are not fulfilled by their biological father. In addition, there are several factors that hinder the implementation of post-divorce child rights, including economic factors, independence of ex-wife, relationship between ex-husband and ex-wife who post-divorce is not good, the ex-husband has remarried, and the complicated and high cost of the application for the execution of post-divorce child maintenance rights is neglected by the ex-husband. The legal effort taken to fight for the right to support children post-divorce granted by the Religious Courts is through execution, but during 2020 to 2023 no one has ever registered an application at the Pekanbaru City Religious Court Office.